ANALISIS IMPLEMENTASI KURIKULUM MERDEKA PADA MATA PELAJARAN AKIDAH AKHLAK MIN YOGYAKARTA - Hardiansyah; Muh. Wasith Achadi (LPPM Universitas Muhammadiyah Bulukumba, 2024)
This article aims to analyze how the independent learning curriculum is implemented in the Aqidah Akhlak subject at MIN Yogyakarta. The research method used in this research is using a representative qualitative research approach. From the results of this research, it was found that MIN Yogyakarta has implemented an independent learning curriculum, especially in the subject of moral beliefs and has been running quite effectively, although there are still several obstacles, namely: teachers are still adapting to the new curriculum so they still don't understand the concept of the independent curriculum 100 percent, and teachers also sometimes have difficulty finding teaching materials considering that the ministry of religion does not publish textbooks based on the independent curriculum. Keywords: moral beliefs, implementation, independent curriculum.